Açai (Euterpe oleracea Mart.) feeding attenuates dimethylhydrazine-induced rat colon carcinogenesis - Fragoso, Mariana F. [UNESP]; Romualdo, Guilherme R. [UNESP]; Ribeiro, Daniel A.; Barbisan, Luis F. [UNESP] (Elsevier, 2013)
This study investigated the protective effect of spray-dried açaí powder (AP) intake on colon carcinogenesis induced by 1,2-dimethylhydrazine (DMH) in male Wistar rats. After 4. weeks of DMH administrations, the groups were fed with standard diet, a diet containing 2.5% or 5.0% AP or a diet containing 0.2% N-acetylcysteine (NAC) for 10. weeks, using aberrant crypt foci (ACF) as the endpoint. Additionally, two groups were fed with standard diet or a diet containing 5.0% AP for 20. weeks, using colon tumors as the endpoint. In ACF assay, a reduction in the number of aberrant crypts (ACs) and ACF (1-3 AC) were observed in the groups fed with 5.0% AP (37% AC and 47% ACF inhibition, p=. 0.036) and 0.2% NAC (39% AC and 41% ACF inhibition, p=. 0.042). In tumor assay, a reduction in the number of invasive tumors (p<. 0.005) and tumor multiplicity (p=. 0.001) was observed in the group fed with 5.0% AP. Also, a reduction in tumor Ki-67 cell proliferation (p=. 0.003) and net growth index (p=. 0.001) was observed in the group fed with 5.0% AP. Therefore the findings of this study indicate that AP feeding may reduce the development of chemically-induced rat colon carcinogenesis. © 2013 Elsevier Ltd.
Keywords: Aberrant crypt foci; Açaí pulp; Colon carcinogenesis; Spray-dry; acetylcysteine; beta catenin; caspase 3; connexin 43; dimethylhydrazine; Euterpe oleracea extract; Ki 67 antigen; plant extract; unclassified drug; animal cell; animal experiment; animal model; animal tissue; apoptosis; Arecaceae; cancer inhibition; cell proliferation; colon cancer; colon carcinogenesis; controlled study; Euterpe oleracea; fluid intake; food intake; intestine crypt; male; nonhuman; powder; protein expression; rat; spray drying; treatment duration; tumor growth; weight gain